A Petrologic and Noble Gas Isotopic Study of New Basaltic Eucrite Grove Mountains 13001 from Antarctica - Chuantong Zhang; Bingkui Miao; Huaiyu He; Hongyi Chen; P. M. Ranjith; Qinglin Xie (Minerals, 2021)
Howardite-Eucrite-Diogenite (HED) meteorite clan is a potential group of planetary materials which provides significant clues to understand the formation and evolution of the solar system. Grove Mountains (GRV) 13001 is a new member of HED meteorite, recovered from the Grove Mountains of Antarctica by the Chinese National Antarctic Research Expedition. This research work presents a comprehensive study of the petrology and mineralogy, chemical composition, noble gas isotopes, cosmic-ray exposure (CRE) age and nominal gas retention age for the meteorite GRV 13001. The output data indicate that GRV 13001 is a monomict basaltic eucrite with typical ophitic/subophitic texture, and it consists mainly of low-Ca pyroxene and plagioclase with normal eucritic chemical compositions. The noble gas based CRE age of the GRV 13001 is approximately 29.9 ± 3.0 Ma, which deviates from the major impact events or periods on the HED parent body. Additionally, the U,Th-4He and 40K-40Ar gas retention ages of this meteorite are ~2.5 to 4.0 Ga and ~3.6 to 4.1 Ga, respectively. Based on the noble gases isotopes and the corresponding ages, GRV 13001 may have experienced intense impact processes during brecciation, and weak thermal event after the ejection event at approximately 30 Ma.